Separating Concerns in Programming: Data, Control and Actions - Kollár, Ján; Porubän, Jaroslav; Václavík, Peter (Computing and Informatics, 2012)
A multi-paradigm language provides an opportunity to a user for exploiting more programming methodologies. It simplifies the language syntax, and extends the application areas by the extended semantics. That is why multi-paradigm languages can align a problem in wider application areas and more flexibly than that based on a single paradigm. In this paper, we present the idea of separating three essential concerns of programming currently being implemented in PFL -- a process functional language. We separate data, control, and actions by the definition of a purely control structure. Then, by the structured application of a structure of actions to a purely control structure, we will express the computation of activated actions in a structured way, considering explicitly defined synchronization in computation.